2015
DOI: 10.1089/ten.tea.2014.0282
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Strontium to a Chondrogenic Medium Promotes Chondrogenic Differentiation of Human Dedifferentiated Fat Cells

Abstract: Dedifferentiated fat cells (DFAT cells) isolated from adipose tissue have been demonstrated to differentiate into chondrogenic cells in vitro. Nevertheless, an efficient method to facilitate its chondrogenic differentiation is still unexplored, hampering the extensive application of these cells in cartilage regeneration therapies. Here we provide the evidence that supplementation of strontium ions (Sr) in a chondrogenic medium (CM) significantly promotes early chondrogenic differentiation of DFAT cells. Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…After 7 days, fat cells have attached to the ceiling; the medium is now removed and the flask is re‐inverted (i.e., the ceiling now becomes the floor of the flask). Fresh medium is added to barely cover the bottom of the flask to allow cells to continue their expansion (Kaida, Honda, Hashimoto, Tanaka, & Baba, ; Kishimoto et al., ; Matsumoto et al., ; Okita et al., ; Sakamoto, Hashimoto, Kishimoto, Honda, & Matsumoto, ; Sakuma et al., ). Adipocytes that have attached to the inner surface of the flask during the ceiling culture divide asymmetrically and produce fibroblast‐like cells.…”
Section: Characteristics Of Human Dedifferentiated Fat Cells—in Vitromentioning
confidence: 99%
See 4 more Smart Citations
“…After 7 days, fat cells have attached to the ceiling; the medium is now removed and the flask is re‐inverted (i.e., the ceiling now becomes the floor of the flask). Fresh medium is added to barely cover the bottom of the flask to allow cells to continue their expansion (Kaida, Honda, Hashimoto, Tanaka, & Baba, ; Kishimoto et al., ; Matsumoto et al., ; Okita et al., ; Sakamoto, Hashimoto, Kishimoto, Honda, & Matsumoto, ; Sakuma et al., ). Adipocytes that have attached to the inner surface of the flask during the ceiling culture divide asymmetrically and produce fibroblast‐like cells.…”
Section: Characteristics Of Human Dedifferentiated Fat Cells—in Vitromentioning
confidence: 99%
“…The cell transplants were harvested after 3 months and were stained by safranin O and alcian blue to evaluate the chondrogenic differentiation of DFAT cells. A reticulated structure, rather than dense and large cartilage‐like tissue, was observed (Okita et al., ). Other groups have reported that fat pads with blood vessels were formed when DFAT cells were injected subcutaneously in the sternum of mice (Nobusue et al., ).…”
Section: Dfat Cells For Oral and Maxillofacial Tissue Engineering—in mentioning
confidence: 99%
See 3 more Smart Citations